2017
DOI: 10.1016/j.agrformet.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Timing of cherry tree blooming: Contrasting effects of rising winter low temperatures and early spring temperatures

Abstract: Phenology reflects the interplay of climate and biological development. Early spring phenological phenomena are particularly important because the end of diapause or dormancy is related not only to heat accumulation in the early spring but also probably to winter low temperatures. Although a warmer winter can reduce overwintering mortality in many insects and plants, it also reduces the accumulation of chilling time that often triggers the end of diapause or dormancy. We examined a continuous 67-year time seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
(96 reference statements)
1
22
0
Order By: Relevance
“…The effect of chilling hours on precocity can be clearly seen, with a reduction of about one day for every 62 CH, within the limits of the experiment (up to around 1000 CH). A similar pattern was observed in apple (Noar et al, 2003), pear (Herter et al, 2001), grapevine (Dokoozlian, 1999), peach (Bruckner et al, 2010;Sugiura et al, 2010), apricot (Campoy et al, 2011) and cherry (Shi et al, 2017) trees, in which reduced budburst time was observed with increased chilling exposure time.…”
Section: Resultssupporting
confidence: 69%
“…The effect of chilling hours on precocity can be clearly seen, with a reduction of about one day for every 62 CH, within the limits of the experiment (up to around 1000 CH). A similar pattern was observed in apple (Noar et al, 2003), pear (Herter et al, 2001), grapevine (Dokoozlian, 1999), peach (Bruckner et al, 2010;Sugiura et al, 2010), apricot (Campoy et al, 2011) and cherry (Shi et al, 2017) trees, in which reduced budburst time was observed with increased chilling exposure time.…”
Section: Resultssupporting
confidence: 69%
“…To compare them, we used three datasets of bamboos (datasets 4-6) with different floating ratios, i.e., 3.08%, −4.35%, and 0.43% (Figure 6d-f). The golden ratio was used to divide a dataset into two parts: training set and test set [24]. In practice, we hoped to use a small number of leaves to obtain the estimates of floating ratio in the SGE and fitted results in the GAM.…”
Section: Comparison Between a Non-parametric Model And The Gielis Equmentioning
confidence: 99%
“…However, warming climate may also lengthen the time required for meeting the chilling requirement in plants, resulting in delayed leaf unfolding (Ford, Harrington, Bansal, Gould, & St Clair, 2016;Murray, Cannell, & Smith, 1989;Yu, Luedeling, & Xu, 2010). Therefore, the temperature response of spring leaf phenology to climate warming is complex due to variations of forcing and chilling unit accumulation (Fu et al, 2015;Keenan, 2015;Luedeling & Gassner, 2012;Luedeling, Guo, Dai, Leslie, & Blanke, 2013;Shi et al, 2017;Wang, Ge, Dai, & Dai, 2015). Fu et al (2015) reported that spring leaf unfolding became less sensitive to temperature in the period of 1999-2013 as compared to 1980-1994 and stated that the observed decline in temperature sensitivity (S T , shift in days per degree Celsius) is likely to be caused by reduced chilling associated with warming.…”
mentioning
confidence: 99%